Immunopathogenesis of severe acute respiratory syndrome coronavirus-2: evolving knowledge and its current status - Nitin Saksena (Open Exploration Publishing Inc., 2021)
As the severe acute respiratory syndrome coronavirus (SARS-CoV)-2 is a new virus, the current knowledge on the immunopathogenesis of this newly emerged SARS-CoV-2 is beginning to unravel with intensive ongoing global research efforts. Although a plethora of new studies have been published in a short space of time describing how the virus causes disease and incurs insults on the host immune system and the underlying immunopathogenic mechanisms remain to be elucidated. Thus, the discussion in this review is based on the most current knowledge on the immunopathogenesis of SARS-CoV-2 that has emerged in the past 12 months. The main objective is to shed light on the most current concepts in immunopathological aspects of the lung, bloodstream, and brain caused by the SARS-CoV-2, which has led to the current pandemic resulting in > 100 million infections and > 2 million deaths, and ongoing.